1980
DOI: 10.1111/j.1365-246x.1980.tb04841.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism and K--Ar ages of Lower Ordovician and Upper Silurian--Lower Devonian rocks from north-west Argentina

Abstract: In this paper we present palaeomagnetic data from 87 hand samples collected in a sequence of tuffs and shales (Suri Formation) of Llanvirnian age, exposed in north-western Argentina (27" 47'S, 68" 06'W). After cleaning, the majority of samples showed reversed polarity and yielded a palaeomagnetic pole at 5.9" E, 8.5" S (ag5 = 5.9'). They also showed reversals of declination and inclination at the top of the sequence, which we have associated with geomagnetic excursions. Whole rock K-Ar age determinations sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Clockwise rotations around vertical axis were observed in Ordovician rocks of the Famatina Ranges (Valencio et al 1980;Conti et al 1996;Spagnuolo et al 2008), the NW Pampean Ranges and the Eastern Puna (Conti et al 1996), whereas counter-clockwise rotations have been found in the Western Puna (Forsythe et al 1993;Rapalini et al 2002). The Famatinian magmatic arc, created by subduction of the Iapetus oceanic plate under the southwestern Gondwana margin that eventually led to the collision of Precordillera probably developed a negative roll back that caused the formation of an important back arc basin with significant extension that led to production of quasi-oceanic crust at some places.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Clockwise rotations around vertical axis were observed in Ordovician rocks of the Famatina Ranges (Valencio et al 1980;Conti et al 1996;Spagnuolo et al 2008), the NW Pampean Ranges and the Eastern Puna (Conti et al 1996), whereas counter-clockwise rotations have been found in the Western Puna (Forsythe et al 1993;Rapalini et al 2002). The Famatinian magmatic arc, created by subduction of the Iapetus oceanic plate under the southwestern Gondwana margin that eventually led to the collision of Precordillera probably developed a negative roll back that caused the formation of an important back arc basin with significant extension that led to production of quasi-oceanic crust at some places.…”
Section: Discussionmentioning
confidence: 92%
“…Clockwise rotations (Famatina Range, NW Pampean Ranges and Eastern Puna) Conti et al (1996) carried out paleomagnetic studies in Lower-Middle Ordovician sedimentary and volcanic units (Susques and Acoite Fms) of the Eastern Puna, in the Early Ordovician Cuchiyaco Granodiorite of the NW Pampean Ranges (Table 1), and reassessed and reinterpreted the results of Valencio et al (1980) in the late Early Ordovician volcanic and volcanoclastic Suri and Las Planchadas formations in the Famatina Ranges. All these rocks provided similar paleomagnetic results, despite the different lithologies, magnetic carriers and locations separated by several 100 km.…”
Section: Paleomagnetic Polesmentioning
confidence: 98%
See 2 more Smart Citations
“…The reconstruction of Gondwana for the Early Ordovician, based on palaeomagnetic evidence (Vilas & Valencio, 1978;Valencio et aL, 1980), placed Argentina at a latitude of about 20°-30°S; calculated from data in Valencio et al, 1980 (Fig. 3).…”
Section: To P 405)mentioning
confidence: 99%